Evaluation of the shelf life of minimally processed cassava treated with antioxidant solution and edible cassava starch-based film - Castro, Juliana Cristina (2024)
The practicality of the easy preparation of minimally processed cassava makes this market segment a viable alternative for adding value to the product. However, there is an intensification of the alterations due to physiological deterioration of the roots in storage. In light of this, the aim of this study was to evaluate cooking time, respiration rate and physicochemical properties during the shelf life of minimally processed cassava treated with preservative antioxidant solution, cassava starch-based film-forming solution and the set of antioxidant solution and film, in addition to the control treatment. All treatments were evaluated at zero, three, six, nine, 12 and 15 days of storage under refrigeration at 4 ºC. The following analyses were conducted: colorimetry, browning index, moisture, weight loss, pH, acidity, shear force, compressive force, cooking time and respiration rate. The data were submitted to analysis of variance with repeated measures and comparison of means using Tukey's test at 5% significance. It was found that the treatments with film, preservative solution and both applied to the roots of minimally processed cassava presented the same shelf life as the control treatment. However, cassava treated only with film had higher values in respiration and acidity and although the results showed a significant difference, the preservative solution showed promising results that warrant further research in view of new formulations and tests to assess quality maintenance and storage time.